Novel Trusted Hierarchy Construction for RFID Sensor–Based MANETs Using ECCs. Issue 1 (1st February 2015) - Kumar, Adarsh; Gopal, Krishna; Aggarwal, Alok
Abstract : In resource‐constrained, low‐cost, radio‐frequency identification (RFID) sensor–based mobile ad hoc networks (MANETs), ensuring security without performance degradation is a major challenge. This paper introduces a novel combination of steps in lightweight protocol integration to provide a secure network for RFID sensor–based MANETs using error‐correcting codes (ECCs). The proposed scheme chooses a quasi‐cyclic ECC. Key pairs are generated using the ECC for establishing a secure message communication. Probability analysis shows that code‐based identification; key generation; and authentication and trust management schemes protect the network from Sybil, eclipse, and de‐synchronization attacks. A lightweight model for the proposed sequence of steps is designed and analyzed using an Alloy analyzer. Results show that selection processes with ten nodes and five subgroup controllers identify attacks in only a few milliseconds. Margrave policy analysis shows that there is no conflict among the roles of network members.